Pina Bausch - Climenhaga, Royd (London : Routledge, 2009)
An Artistic and Contextual History - What is Said - Kontakthof in Context - Practical Exercises
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Bausch, Pina